Influence of the surface roughness of coated and uncoated papers on the digital print mottle - Jurič, Ivana; Ranđelović, Danijela; Karlović, Igor; Tomić, Ivana (Journal of Graphic Engineering and Design, 2023)
Many factors influence the occurrence of print mottle in prints. In printing process three main components are involved: printing press, substrate and toner. They can be considered as separate components, but in most cases their interaction influences the quality of the print. The goal of this work was to examine the influence of surface roughness of different types of paper (coated and uncoated on print mottle of electrophotographic digital prints. We set up a hypothesis that print mottle will be more apparent on rougher surfaces. In the experimental part we printed four different substrates with different surface properties on electrophotographic printing press. Morphology of the papers surface was analysed using atomic force microscopy (AFM) from which surface properties were calculated. For print mottle characterization Gray level co-occurrence matrix (GLCM) method was used. Based on the measurements and results we can conclude, contrary to the initial hypothesis, that uncoated papers with rougher surfaces produce smaller print mottle values.